The Synthesis of Two Regioisomeric Aldehydes with a Tetrahydrobenzo[b]thiophene Scaffold and Their Application in Solvent-Free Intramolecular 1,3-Dipolar Cycloaddition Reactions - Tenora, L.; Man, S.; Van Den Berge, E.; Potáček, M. (Synthesis, 2016)
The paper describes the synthesis of two regioisomeric 2-amino-3-formyl- and 3-amino-2-formyl-substituted derivatives of tetrahydrobenzo[b]thiophene and their subsequent thermally initiated reactions with secondary amines to give azomethine ylides that undergo intramolecular 1,3-dipolar cycloadditions. In this way, two series of new fused heterocyclic compounds with three stereogenic centers were prepared. The compounds were identified and their structures were determined.
Keywords: dipolar cycloadditions; benzothiophenes; polycycles; heterocycles; azomethine ylides